Applied Evolutionary Economics and Economic Geography 2007
DOI: 10.4337/9781847205391.00024
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Territorial Adoption of New Technologies: A Spatial Econometric Approach

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…initiatives for digitising major parts of their collections but the same promise of digitisation is yet to be realised by many smaller and regional organisations. In particular, south European cultural heritage institutions appear to be slower adopters of ICT (Information and Communication Technologies) compared to their northern counterparts and the reasons for such lack of uptake are complex (Peacock 2008;Gombault et al 2016), despite the fact that heritage in such regions is rich, diverse and forms a key strategic resource for economic development (see, e.g., Bonaccorsi et al 2007). Semantic Web technologies can significantly benefit digitised collections by disclosing information in a scalable and interoperable way, aggregating previously heterogeneous and siloed data (Benjamins et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…initiatives for digitising major parts of their collections but the same promise of digitisation is yet to be realised by many smaller and regional organisations. In particular, south European cultural heritage institutions appear to be slower adopters of ICT (Information and Communication Technologies) compared to their northern counterparts and the reasons for such lack of uptake are complex (Peacock 2008;Gombault et al 2016), despite the fact that heritage in such regions is rich, diverse and forms a key strategic resource for economic development (see, e.g., Bonaccorsi et al 2007). Semantic Web technologies can significantly benefit digitised collections by disclosing information in a scalable and interoperable way, aggregating previously heterogeneous and siloed data (Benjamins et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There are thousands of small-and medium-sized museums across Europe that house important collections, but have a very limited or even a non-existent digital presence, with a variety of factors that can cause this. Lack of budget, limited human resources, slow technology acceptance, organisational attitudes and bureaucracy associated with decision-making in public institutions (Gombault et al 2016), but also the geographical location of the museum, the museum type and reasons internal to the organisation such as leadership (Bonaccorsi, et al, 2007;Peacock, 2008) can provide hindrances for fulfilling the potential of digitisation and receiving the benefits of an effective adoption of ICT. Similar obstacles in the provision of interoperable online access to archival holdings and metadata have been reported by a comparative survey of the views of archivists from Croatian, Finnish and Swedish archive (Tanacković Faletar et al 2017).…”
Section: Overview Of the Case Studymentioning
confidence: 99%
“…Italy is an ICT laggard as compared with the U.S. or other European countries. Bonaccorsi, Piscitello, and Rossi (2006) explored ICT diffusion in Italy, using provinces as a geographical unit of analysis. They found that sectoral composition, technological endowment and absorptive capacity at the regional level, as well as firm characteristics, are factors able to explain the territorial distribution of ICT firms.…”
mentioning
confidence: 99%